Pengaruh Relationship Marketing Terhadap Loyalitas Pelanggan IM3 OOREDOO (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Nur Lailiyah; Yustina Chrismardani (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The research aims to determine relationship marketing which consists of trust, communication, competence commitment and cooperation to customer loyalty IM3 Ooredoo (Study on Students of the Faculty of Economics and Business, University of Trunojoyo Madura) from 2017 to 2020. Sampling in this study used purposive sampling and analyzed using multiple linear regression analysis. The results of this study indicate that relationship marketing which consists of trust, communication, competence, commitment and cooperation has a simultaneous effect on customer loyalty, and the variables trust, communication, competence, commitment and cooperation have a partially significant effect on customer loyalty.